RELEVANSI FILSAFAT IBNU SINA TERHADAP PEMBANGUNAN PERADABAN BERKELANJUTAN DI ABAD KE-21 - Olga Yosnita Sari; Nunu Burhanuddin (SOSPENDIS : Sosiologi Pendidikan dan Pendidikan IPS, 2025)
As Ibn Sina is an important figure in the history of Islamic thought and science, his philosophy is highly relevant to the issues facing the 21st century to build a sustainable civilization. Ibn Sina's works, especially in the fields of epistemology, ethics, and science, provide perspectives that can be applied to address contemporary issues such as the health crisis, climate change, and social injustice. Ibn Sina's philosophy focuses on the concepts of balance and harmony, which can help us understand how important integration between technological advancement and environmental preservation is. In addition, the holistic approach he offers to understanding nature and humans can help in making policies that are more just and sustainable. Ibn Sina's philosophy of the pursuit of knowledge and the development of human potential is crucial to education as it helps the next generation become more sensitive to the world's problems and take responsibility for their future. Therefore, applying the principles of Ibn Sina's philosophy can help build a civilization in the 21st century that is stable, balanced and just. The method used is a descriptive qualitative approach that combines contextual, philosophical, and historical reviews. Data were collected from secondary literature related to sustainable development as well as Ibn Sina's most important works, such as Kitab Al-Shifa and Canon of Medicine. This study shows that Ibn Sina's ideas on epistemology, environmental ethics, and holistic education are useful for solving the world's current problems. In Ibn Sina's philosophy, the concept of balance between humans, nature and God can be used as a philosophical foundation to build harmony between material and spiritual progress. This study found that Ibn Sina's philosophy is instrumental in building a more humane, ethical and inclusive sustainable development paradigm. The conclusion is that these findings can serve as a reference for policy officials and academics to incorporate ethical values and spirituality into global development strategies.